Open innovation within high-tech SMEs: A study of the entrepreneurial founder's influence on open innovation practices. (May 2021) - Barrett, Gillian; Dooley, Lawrence; Bogue, Joe
Abstract: This study aims to deepen our knowledge of the SME 'human' role within open innovation adoption. To achieve this, we explore how the SME leader, namely the founder/CEO managerial characteristics influence the SMEs open innovation adoption dynamics (i.e. mechanisms, partners, motives and sequence of adoption). The empirical analysis is based on seven Irish medical device SME case studies achieving high growth ambitions at an international level. Our findings demonstrate that SME open innovation adoption is exemplified by a project based as opposed to an organisational level rationale and a natural tendency to pivot back towards the closed paradigm through a 'switchback' strategy once the need has been addressed. In turn, SMEs develop open innovation capabilities on a project by project basis and mature as a consequence, thus highlighting the importance of the 'doing, using, interacting' mode of learning within SME OI development. Furthermore, SMEs tend to adopt a common sequential and temporal pathway commencing with a commercialisation focus through the outside-in mode followed by a complex, coupled co-creation mode. This study also provides insights into how the founder/CEO's characteristics influence OI adoption dynamics using the West and Bogers (2014) obtaining, integrating and commercialising framework thus extending upper echelons theory (UET) and strengthening the connection between open innovation and entrepreneurship theory. Highlights: A 'human' micro-level perspective of the SME leader (founder/CEO) within open innovation adoption. Identifies the SME open innovation dynamics and highlights the differentiating factors of adoption in the SME context. SME open innovation is exemplified by a project based 'operational' rationale and a 'switchback' to closed practices. SMEs tend to adopt a sequential and temporal pathway, developing innovation capabilities and maturing on a project basis. This research establishes the connection between open innovation and entrepreneurship theory.